Seasonal Propagation of Green Algae in Kara–Kyr Lake Bukhara Region - Avezova, Muhayyo (Центр Научных Публикаций (buxdu.uz), 2021)
Identifying the types of microscopic algae that are prevalent in water basins and studying their importance is one of the most pressing issues awaiting solution today. In this regard, research has been conducted to observe the classification of Lake Kara-Kyr in Bukhara region and the study of the types of microscopic algae in the water, the seasonal propagation. Commonly accepted algal methods and plant identifiers were used to determine the types of microscopic algae. According to the results, a total of 41 species belonging to the Chlorophyta division were identified in Kara-Kyr Lake. The seasonal propagation of the identified species was analyzed and 35 species were recorded in spring, 38 in summer, 28 in autumn, and 11 in winter.